Tourist awareness and its relationship in the academic performance of undergraduate students - Caballero-Copara, Liliana (2021)
The main objective of this research was to establish the level of relationship between tourism awareness and the academic performance of the students of the Tourism and Hospitality EAP of the UNHEVAL, 2019. The research is of a type and of a descriptive-correlational level , where the transversal research design was used, pointing out that this type of design collects data in a single moment, in a single time. To answer the questions raised as research problems and meet the objectives of this work, two questionnaires were prepared addressed to the 40 students, the process of validity and reliability of the instruments, as well as The treatment of the data was processed with the statistical package SPSS V-25. The results of the investigation have reported that the correlation is positive low (rho = 0.238) between the variables, which shows that tourist awareness and academic performance have a positive low relationship, but not significantly since the bilateral significance (0.139) is less than 0.05. Coming to the conclusion that there is a low positive correlation between the variables studied.